Үндэсний аюулгүй байдлын гадаад, дотоод орчны хувьсал өөрчлөлт, болзошгүй аюул, сорилтын тухай төсөөлөл - П.Мягмарсүрэн (Politology, 2023)
Accorciing to US researchers conclusion "we are living rn the period that is full of unpredictable developnrents ' Therefore this article presents current situation of external and internal environments of Mongolia s National Securrty, which becomes a part of the international security, and attempts to picture its near-term developments, possible threats, and ordeals.